ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS BAJO BARAT - Fitriana Ibrahim; Bakti Rahayu; Ajeng Anggreny Ibrahim; Devianti Tandiallo (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Background: Stunting is a nutritional problem experienced by toddlers with a height characteristic that is less than the height index of toddlers 2-5 years. Stunting can have an impact on children's health and intelligence. Objective: To see the factors related to stunting in toddlers aged 24-59 months in the Bajo Barat region. Methods: Using an analytical survey with a cross sectional study approach. The population is 83 with a sample of 45. Probability sampling is used as a sampling technique and Slovin's formula is used to determine sample size.. Collecting data by distributing questionnaires. The data was processed using SPSS version 25 and analyzed by univariate and bivariate with chi-square statistical test and presented in the form of frequency distribution table and analysis. Results: Bivariate analysis found the relationship between exclusive breastfeeding and stunting cases (ρ-Value = 0.003), education level with the incidence of Stunting ( -Value = 0.003 ) and Family Income with the incidence of Stunting ( -Value = 0.000). Conclusion: There is a relationship between exclusive breastfeeding, education level and family income with the incidence of stunting in toddlers aged 24-59 months in the Puskesmas Bajo Barat work area